Animation and interactive system for virtual aquatic animals in an undersea world - Goh, Albert Lian Lai (2008)
The goal of this project is to develop a mathematical and computational framework for generating realistic and fascinating motions of soft or highly flexible bodies with emphasis on locomotions of aquatic animal.